Performance of Beef Replacement Heifers Supplemented with Dried Distillers Grains or a Mixture of Soybean Meal and Ground Sorghum Grain - C. J. McMullen; J. R. Jaeger; K. R. Harmoney; J. W. Waggoner; K C Olson (Kansas Agricultural Experiment Station Research Reports, 2016)
The feed, labor, and equipment costs of developing heifers in a confined feeding system are relatively high. High Plains beef producers can reduce input costs by developing heifers on dormant native range; however, heifers are typically unable to consume sufficient crude protein (CP) from the low-quality (<7% CP) forage base. Insufficient dietary protein reduces forage digestion and performance potential of growing heifers. Supplementing protein when forage quality was poor has previously been reported to increase forage intake and forage digestibility, which resulted in acceptable levels of performance. An efficient means of supplying supplemental protein to heifers consuming low-quality forage is through the use of supplements with relatively high crude protein concentrations (>30% CP). Traditionally, producers have used oilseed meals in this capacity, but with the expansion of the ethanol industry, dried distillers grains with solubles (DDG) have become widely available as an alternative protein source for producers in corn and sorghum-producing regions. Adequate heifer body weight and body condition score at first breeding are essential to minimize age at first calving and to increase lifetime productivity. Therefore, the objective of our study was to evaluate the effects of supplementation of DDG or an approximately isonitrogenous mixture of soybean meal and ground sorghum grain on growth and reproductive performance of replacement heifers grazing low-quality, dormant native range.
Keywords: Beef Cattle Research